TINJAUAN UMUM PERJANJIAN KREDIT DAN LEMBAGA PERKREDITAN DESA (LPD) - Jaya, M.Hum, Dr. Drs. M.S Chandra (Fakultas Hukum Universitas Dwijendra, 2015)
ABSTRACTÂ The credit agreement is an agreement to lend money with or without interest, or certain items must be returned in accordance with their respective values at the time agreed upon. Customary law Bali, often referred to Awig-Awig. Awig-awig were made by members of the community together with prajuru / custom Kelihan both written and unwritten, that are not contrary to Pancasila and the Constitution of 1945. In implementing the credit agreement in LPD, an important element is based on the consent of the Kelihan or Bendesa Indigenous Peoples.Thus it can be said that the borrowing is done without consent or Bendesa Indigenous Customary Kelihan is invalid. Completion conducted by Village Credit Institutions in case of bad credit it does not always have to go through Paruman prajuru Village People. If the only way to approach the credit decision has paid off his credit there is no need to mention the Paruman.Â Keywords: Credit Agreement, Village Credit Institutions.Â